The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1097/01.rli.0000078762.72335.57
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Diffusivity Imaging at 3.0 T for the Detection of Degenerative Changes

Abstract: In a trypsin-based arthritis model, the spatial localization and quantification of damaged areas have been shown to be possible on a whole body 3.0 T MR system. Measurement times achieved for these high spatial resolution studies make in vivo investigations feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…An alternative model of osteoarthritis is the use of trypsin to induce the degeneration of proteoglycan (66)(67)(68). Trypsin is a 24 kDa endopeptidase commonly produced in the pancreas for the digestion of dietary amino acids (69).…”
Section: Models Of Osteoarthritis In Articular Cartilagementioning
confidence: 99%
“…An alternative model of osteoarthritis is the use of trypsin to induce the degeneration of proteoglycan (66)(67)(68). Trypsin is a 24 kDa endopeptidase commonly produced in the pancreas for the digestion of dietary amino acids (69).…”
Section: Models Of Osteoarthritis In Articular Cartilagementioning
confidence: 99%
“…For the trypsin group, 5 mg of trypsin (Sigma Chemical Co., St. Louis) in 40 ml Tris buffer was injected into the nucleus pulposus. Trypsin catalyzes the hydrolysis of peptide bonds and has been used previously to dissolve denatured collagen leaving the remaining collagen intact (Berg et al, 2003).…”
Section: Experimental Groupsmentioning
confidence: 99%
“…The now available high-field MR systems offer high intrinsic signal thus allowing a further increase in spatial resolution. For neurological applications it has been demonstrated that the higher spatial resolution improves detail delineation and thus diagnostic accuracy [1][2][3][4][5]. Wholebody applications are now being evaluated at 3 T [6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%